Saúde indígena e Serviço Social: uma análise das experiências publicadas nos anais do ENPESS e CBAS (2016 a 2022) - Filgueira, Mayara Gama (Brasil, 2025)
The general objective of this Course Completion Work was to analyze the academic production of Brazilian Social Service that has as its centrality the theme of indigenous health, based on the Literature Review in Annals of the National Meeting of Researchers in Social Service (ENPESS, editions 2018 and 2022) and the Brazilian Congress of Social Workers (CBAS, 2016, 2019 and 2022 editions). As specific: problematize, at a theoretical level, the topic of indigenous health and its relationship with Social Services; Characterize the works present in the Annals of ENPESS and CBAS; Reflect on the academic production of the Annals that deal with indigenous health, highlighting the importance of Social Work in this context. As a methodology, it is a bibliographical research that had as a source of information, in addition to the authors who deal with the topic, the productions published in the highlighted congresses. The results indicate a total of 28 works/articles in the five Annals researched that allude to the indigenous issue. However, in the particularity of health policy, only four were found, which were analyzed according to their content. The results indicate that, in recent years, despite the approach of Social Service to the indigenous issue, production that favors the health field is still incipient. On the other hand, it is necessary to reflect on the importance that this profession has in working with indigenous peoples in their health conditions as a social right.